Peer observation of teaching at U.Porto: a multidisciplinary approach to peer observation of teaching - João Pedro Pêgo (2013)
The Peer Observation of Teaching at U. Porto ("De Par em Par na U.Porto") project is a peer observation of teaching (POT) program whose main goal was, since the beginning, to use peer observation for teachers' training purpose. It started as pilot program between the Faculty of Engineering and the Psychology and Education Science Faculty of the University of Porto, in 2009. Since 2010 it has been widespread to the most of the 14 Faculties and Schools of the University of Porto, involving over 150 participants in the last three years. Peer observation arises from critical friend concept and it is a common practice in several universities. The original feature of POT at Porto University is its multidisciplinary character and its training goal both to observers as to observed teachers. The present communication presents POT-UP's structure in a multidisciplinary context and discusses the emergent question - to what extent multidisciplinary peer observation promotes teacher training?